Critiquing nursing research - Cutcliffe, John R., 1966- (Andrews UK, 2014)
This second edition of Quay Books' bestselling title retains all of the successful features of the first, plus additional material including a chapter on European psychiatric research. Foreword by Kevin Gournay.